The Influence of Marketing Strategies on Purchase Decisions of Chicken Porridge for Breakfast Among Chicken Porridge Vendors in the Pasar Minggu Area - Madiistriyatno, Harries (Raudhah Publisher, 2024)
This study aims to analyze the influence of marketing strategies on the purchase decisions of chicken porridge as a breakfast choice in the Pasar Minggu area. The research examines the elements of the marketing mix (product, price, place, promotion) and how each factor affects consumer decisions. Data were obtained through a survey of 100 chicken porridge buyers in the Pasar Minggu area. The results indicate that price and promotion factors play a significant role in influencing purchase decisions. The conclusion of this study suggests that chicken porridge vendors should enhance their pricing and promotion strategies to boost sales.